Complete Genome Sequence of a Shiga Toxin-Producing Enterobacter cloacae Clinical Isolate - Carter, Michelle Qiu (Genome Announc, 2017)
Enterobacter cloacae strain M12X01451 was isolated from a patient with mild diarrhea. This strain produces a novel subtype of Shiga toxin 1, Stx1e. The Stx1e-converting prophage in strain M12X01451 is stable and can infect other bacteria following induction. Here we report the complete genome sequence and annotation of strain M12X01451.